2010
DOI: 10.1021/jm9011615
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Epigenetic Small Molecule Induces Expression of the Tumor Suppressor Ras-Association Domain Family 1A and Inhibits Human Prostate Xenograft

Abstract: Epigenetic silencing of Ras-association domain family 1A (RASSF1A) protein in cancer cells results in a disruption of cell cycle control, genetic instability, enhanced cell motility, and apoptotic resistance. Ectopic expression of RASSF1A reverses this tumorigenic phenotype. Thus, small molecules with the ability to restore RASSF1A expression may represent a new class of therapeutic agents. Recently, we designed and synthesized a fluorescent carbazole analogue of mahanine (alkaloid from Murraya koenigii) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…[56] Similar effects were observed in prostate cancer cells treated with a synthetic fluorescent analogue (Ked-4-69) of mahanine. [57] Mahanine and Ked-4-69 appear to judiciously inhibit DNMT translocation. [57] However, further studies are necessary to confirm whether mahanine or its analogs restore RASSF1A without disrupting epigenetic modifications across the genome.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…[56] Similar effects were observed in prostate cancer cells treated with a synthetic fluorescent analogue (Ked-4-69) of mahanine. [57] Mahanine and Ked-4-69 appear to judiciously inhibit DNMT translocation. [57] However, further studies are necessary to confirm whether mahanine or its analogs restore RASSF1A without disrupting epigenetic modifications across the genome.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Evaluation of effects of YK-4-272 on mouse xenograft was performed as previously reported (20). Briefly, male athymic Balb/c nude mice weighing 18–22 g were injected with 0.3 mL of 3×10 6 PC-3 cells in the subcutaneous tissue of the right axillary region of the body.…”
Section: Methodsmentioning
confidence: 99%
“…However, more recent studies showed that curcumin did not cause DNA demethylation in three arbitrarily chosen human cancer cell lines . Mahanine, a plantderived carbazole alkaloid, and a fluorescent carbazole analogue, has been reported to induce the Ras-association domain family 1 (RASSF1) gene in human prostate cancer cells, presumably by inhibiting DNMT activity (Jagadeesh et al, 2007;Sheikh et al, 2010). Nanaomycin A, a quinone antibiotic isolated from a culture of Streptomyces, has been described as the first non S-adenosyl-L-homocysteine (AdoHcy/SAH) analogue acting as a DNMT3B-selective inhibitor that induces genomic demethylation.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…2 inhibited human prostate cancer cell proliferation at 1.5 µM and also showed DNMT inhibition activity without the cytotoxic effects seen with mahanine treatment. Inhibition of DNMT was proposed as the event leading to the restoration of RASSF1A expression (Sheikh et al, 2010).…”
Section: Optimization Of Rg108 Procaine and Mahaninementioning
confidence: 99%